1997
DOI: 10.1111/j.1471-6402.1997.tb00125.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Feminist Versus Psychoanalytic/Dynamic and Other Therapists on Self-Disclosure

Abstract: The Feminist Self‐Disclosure Inventory (FSDI) was developed to assess principles of therapist self‐disclosure as described in the feminist therapy literature. This 18‐item Likert‐type scale was completed in a mailed survey by women psychotherapists (i.e., 41 self‐identified feminist therapists, 34 psychoanalytic/dynamic, and 68 other therapists). Results indicated that the FSDI was comprised of five factors [i.e., Therapist Background (TB), Promotes Liberatory Feelings (PLF), Promotes Egalitarianism (PE), Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…Allen's article on disclosing about sexual orientation provides a case study demonstrating how content and strategy can be combined to use self‐disclosure as a teaching tool. Just as there is growing attention to self‐disclosure in feminist therapy (Simi & Mahalik, 1997), consideration needs to be given to issues related to disclosure in feminist pedagogy such as the content, frequency, and purposes of the disclosures. In addition, it is important for feminist teachers, as they are making decisions about self‐disclosure, to reflect upon their status in the institution, the subject matter about which they are teaching, their personal boundaries, and their knowledge and understanding of their students (Allen & Baber, 1992).…”
Section: Pedagogical Challenges Of Teaching Human Sexualitymentioning
confidence: 99%
“…Allen's article on disclosing about sexual orientation provides a case study demonstrating how content and strategy can be combined to use self‐disclosure as a teaching tool. Just as there is growing attention to self‐disclosure in feminist therapy (Simi & Mahalik, 1997), consideration needs to be given to issues related to disclosure in feminist pedagogy such as the content, frequency, and purposes of the disclosures. In addition, it is important for feminist teachers, as they are making decisions about self‐disclosure, to reflect upon their status in the institution, the subject matter about which they are teaching, their personal boundaries, and their knowledge and understanding of their students (Allen & Baber, 1992).…”
Section: Pedagogical Challenges Of Teaching Human Sexualitymentioning
confidence: 99%
“…Although some researchers have found that informal discussion involving self-disclosure may help strengthen emotional bonds and therapeutic alliance (Goldfried, Burckell, & Eubanks-Carter, 2003; Hill & Knox, 2001) and establish an egalitarian relationship which empowers clients to change (Simi & Mahalik, 1997), other researchers have found results similar to those reported by Martino and colleagues (2009). This research highlights the potential negative effects of informal discussion when counselors share personal information with their clients that is not directly related to treatment.…”
Section: Introductionmentioning
confidence: 67%
“…Personal Self-Disclosure by Therapists Self-disclosure is also a controversial issue among therapists and clients. Simi and Mahalik (1997) found that feminist therapists were more likely than other therapists to use self-disclosure to empower a client, and to disclose personal background information, such as class, political beliefs, and sexual orientation. Simon (1988) found that therapists used self-disclosure to enhance the therapeutic alliance, validate reality, encourage client autonomy, and improve therapist satisfaction.…”
Section: Use Of Touchmentioning
confidence: 98%